2016
DOI: 10.1371/journal.pone.0167798
|View full text |Cite
|
Sign up to set email alerts
|

Varroa destructor Mites Can Nimbly Climb from Flowers onto Foraging Honey Bees

Abstract: Varroa destructor, the introduced parasite of European honey bees associated with massive colony deaths, spreads readily through populations of honey bee colonies, both managed colonies living crowded together in apiaries and wild colonies living widely dispersed in natural settings. Mites are hypothesized to spread between most managed colonies via phoretically riding forager bees when they engage in robbing colonies or they drift between hives. However, widely spaced wild colonies show Varroa infestation des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 30 publications
1
32
0
1
Order By: Relevance
“…found in genotypic composition of mites among the five colonies. As the colony level had only very little influence on the population structure of the parasite, our results suggest that Varroa moves readily among hives at the apiary level, in accordance with other studies (Seeley & Smith, 2015;DeGrandi-Hoffman et al, 2016;Peck et al, 2016;Nolan & Delaplane, 2017). The comparison of the genotypes of the foundress pairs suggested that the association of mites in a multiply infested cell is mainly driven by random choice rather than any specific adaptive behavior of the foundresses: mites neither with the same nor different genotypes preferentially coinvaded cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…found in genotypic composition of mites among the five colonies. As the colony level had only very little influence on the population structure of the parasite, our results suggest that Varroa moves readily among hives at the apiary level, in accordance with other studies (Seeley & Smith, 2015;DeGrandi-Hoffman et al, 2016;Peck et al, 2016;Nolan & Delaplane, 2017). The comparison of the genotypes of the foundress pairs suggested that the association of mites in a multiply infested cell is mainly driven by random choice rather than any specific adaptive behavior of the foundresses: mites neither with the same nor different genotypes preferentially coinvaded cells.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, our AMOVA showed that the genetic variation between individual mites within colonies was most important while only very few differences were found in genotypic composition of mites among the five colonies. As the colony level had only very little influence on the population structure of the parasite, our results suggest that Varroa moves readily among hives at the apiary level, in accordance with other studies (Seeley & Smith, ; DeGrandi‐Hoffman et al ., ; Peck et al ., ; Nolan & Delaplane, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper (Mordecai et al 2015) reports, however, that an avirulent variant of DWV exists in some locations in the UK, so perhaps an avirulent variant of DWValso exists in some of the wild colonies near Ithaca, NY. These colonies are widely spaced , so the spread of V. destructor and DWV between colonies may occur more by vertical transmission (from parent colony to offspring colony, by swarming) than by horizontal transmission (among unrelated colonies; by drifting, robbing, and foraging; see Peck et al 2016). If so, then perhaps the mites and viruses in these wild colonies are evolving avirulence (Ewald 1994;Fries and Camazine 2001), but it seems clear that they are not there yet.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of varroa mites suggest that varroa females feed exclusively on hemolymph (Cabrera et al 2017;Erban et al 2015). Hemolymph surrounds every cell in the hemocoel of most arthropods (Fredrick and Ravichandran 2012;Lawry 2006;Paska et al 2014), and is also a reservoir of nutrients. The abdomen likely contains a high volume of hemolymph.…”
Section: Feeding Preferencementioning
confidence: 99%